Covid-19 diagnosis and mortality in patients with non-ST-elevation myocardial infarction admitted in Italy during the national outbreak. (1st January 2023) - De Luca, Leonardo; Rosato, Stefano; D'Errigo, Paola; Giordani, Barbara; Mureddu, Gian Francesco; Badoni, Gabriella; Seccareccia, Fulvia; Baglio, Giovanni
Abstract: Introduction: We sought to assess the clinical impact of Covid-19 infection on mortality in patients with Non-ST elevation myocardial infarction (NSTEMI) admitted during the national outbreak in Italy. Methods: We analysed a nationwide, comprehensive, and universal administrative database of consecutive NSTEMI patients admitted during lockdown for Covid-19 infection (March, 11st - May 3rd, 2020) and the equivalent periods of the previous 5 years in Italy. The observed rate of 30-day and 6-month all-cause mortality of NSTEMI patients with and without Covid-19 infection during the lockdown was compared with the expected rate of death according to the trend of the previous 5 years. Results: During the period of observation, 48.447 NSTEMI hospitalizations occurred in Italy. Among these, 4981 NSTEMI patients were admitted during the 2020 outbreak: 173 (3.5%) with and 4808 (96.5%) without a Covid-19 diagnosis. According to the 5-year trend, the 2020 expected rate of 30-day and 6-month all-cause mortality was 6.5% and 12.2%, while the observed incidence of death was 8.3% ( p  = 0.001) and 13.6% ( p  = 0.041), respectively. Excluding NSTEMI patients with a Covid-19 diagnosis, the 6-month mortality rate resulted in accordance with the prior 5-year trend. After multiple corrections, the presence of Covid-19 diagnosis resulted one of the independent predictors of all-cause mortality at 30 days [adjusted odds ratio (OR) 4.3; 95% confidence intervals (CI) 2.90–6.23; p  < 0.0001] and 6 months (adjusted OR 3.5; 95% CI: 2.43–5.03; p < 0.0001). Conclusions: During the 2020 national outbreak in Italy, a concomitant diagnosis of Covid-19 in NSTEMI was associated with a significantly higher rate of mortality. Highlights: Our data documented a marked reduction of hospital admissions for NSTEMI during the outbreak for Covid-19 in Italy All-cause death was higher compared with mortality trends for NSTEMI of the same calendar periods in the previous 5 years Excluding NSTEMI with Covid-19 infection, the observed 6-month mortality rate was in accordance with the 5-years trend